2023
DOI: 10.1073/pnas.2219770120
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone regulates proximodistal patterning in fin rays

Melody Harper,
Yinan Hu,
Joan Donahue
et al.

Abstract: Processes that regulate size and patterning along an axis must be highly integrated to generate robust shapes; relative changes in these processes underlie both congenital disease and evolutionary change. Fin length mutants in zebrafish have provided considerable insight into the pathways regulating fin size, yet signals underlying patterning have remained less clear. The bony rays of the fins possess distinct patterning along the proximodistal axis, reflected in the location of ray bifurcations and the length… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Intact fins show transcriptomic differences across the proximodistal axis (Harper et al, 2023;Rabinowitz et al, 2017), and here we identified a robust suite of gene expression patterns that shift as the fin regenerated different proximodistal regions of the organ. Previous transcriptomic analyses of regenerating fins have focused on the early shifts in expression as the tissue initiates regenerative regrowth (Li et al, 2021;Nauroy et al, 2019); we found that there are substantial shifts in expression patterns even after regeneration is underway, as different stages of outgrowth proceed.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Intact fins show transcriptomic differences across the proximodistal axis (Harper et al, 2023;Rabinowitz et al, 2017), and here we identified a robust suite of gene expression patterns that shift as the fin regenerated different proximodistal regions of the organ. Previous transcriptomic analyses of regenerating fins have focused on the early shifts in expression as the tissue initiates regenerative regrowth (Li et al, 2021;Nauroy et al, 2019); we found that there are substantial shifts in expression patterns even after regeneration is underway, as different stages of outgrowth proceed.…”
Section: Discussionmentioning
confidence: 69%
“…scpp7 is proximally enriched during regeneration. Since distal-specific morphologies are regulated by TH (Harper et al, 2023), genes that are expressed in a TH-dependent proximodistal differential are strong candidates for involvement in distal patterning. Of the transcripts showing TH-dependent proximal enrichment, we selected secretory calcium-binding phosphoprotein 7 (scpp7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations